Pemikiran Ulama Sumatera Selatan Abad XX dan Pengaruhnya terhadap Peradaban - Nurseri Hasnah Nasution (UIN Sumatera Utara Medan, 2017)
The cleric of South Sumatra is a central figure with wide authority. They have a multifunction with polymorphic leadership. Historical facts show that they are civilization actors who respond to various problems of South Sumatra in the twentieth century. These problems are characterized by the religious phenomenon of postmodernism and the problems of religious articulation diversity. To respond to these phenomena and problems, some South Sumatra clerics such as K.H. Anwar Kumpul, K.H. Muhammad Zen Syukri, and K.H. Zainal Abidin Fikry formulated some thoughts. Their thinking influenced the progress of civilization in South Sumatra.Subject matter of thought K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry consists of: political participation, patriotism and nationalism, secondary and higher education, gender equality, social change. This thinking is characterized by the actualization of traditions and moderns based on tauhid.Thought K.H. Anwar Kumpul, K.H. Muhammad Zen Syukri, K.H. Zainal Abidin Fikry effect on the progress of civilization in South Sumatra. This study deconstructs the collective perceptions and memories introduced by Jeroen Peeters. He mentioned that the scholars who did the modernization in South Sumatra in the XX century were Muhammadiyah scholars, also not entirely true. Proven, structurally and culturally, K.H. Anwar, K.H. Muhammad Zen Syukri, and K.H. Zainal Abidin Fikry is a NU scholar, but they are active in modernization in South Sumatra in the twentieth century.